2022
DOI: 10.4081/jphia.2022.2184
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from the World Health Organization’s late initial response to the 2014-2016 Ebola outbreak in West Africa

Abstract: Monkeypox (MPX) is a viral zoonosis with lesions like smallpox. Though rare in Nigeria, sporadic outbreaks have been reported in 17 states since September 2017. Unfortunately, the COVID-19 pandemic has further reduced surveillance and reporting of MPX disease. This study seeks to assess the effect of an enhanced surveillance approach to detect MPX cases and measure the cumulative incidence of MPX in priority states in Nigeria. We identified three priority states (Rivers, Delta and Bayelsa) and their Local Gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Before 2018, no outbreaks had been reported between the outbreak in Sangha Mbaéré prefecture during 1983-1984 and the outbreak in Mbomou prefecture in 2001 (17,18). We observed a similar pattern in areas of sporadic endemicity, where recent outbreaks occurred in Cameroon in 2018 after 29 years of absence (30), in Sierra Leone in 2014 after 44 years (31), and in Nigeria in 2017 after 39 years (32). More generally, the recent increase in the number of outbreaks in CAR has been mirrored elsewhere, in West Africa and the Congo Basin region, and seems to reflect improvements in surveillance, as well as increased viral circulation in a region experiencing major ecologic disturbances (33).…”
Section: Discussionsupporting
confidence: 72%
“…Before 2018, no outbreaks had been reported between the outbreak in Sangha Mbaéré prefecture during 1983-1984 and the outbreak in Mbomou prefecture in 2001 (17,18). We observed a similar pattern in areas of sporadic endemicity, where recent outbreaks occurred in Cameroon in 2018 after 29 years of absence (30), in Sierra Leone in 2014 after 44 years (31), and in Nigeria in 2017 after 39 years (32). More generally, the recent increase in the number of outbreaks in CAR has been mirrored elsewhere, in West Africa and the Congo Basin region, and seems to reflect improvements in surveillance, as well as increased viral circulation in a region experiencing major ecologic disturbances (33).…”
Section: Discussionsupporting
confidence: 72%
“…3 Pool prevalences forest plots of the cutaneous lesion characteristics and sites long-term follow-up cohort assessments. More studies from outside Africa, now that 37 non-endemic countries have reported cases are necessary to contribute to the growing volume of data, in addition to the increasing number of studies appearing in 2022 from African countries [84][85][86]. Even more, assessing the impact of spreading events, including the pride parties and festivals on Grand Canary island in Spain or Belgium, needs better evaluations [18,36,41,42,[71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with MPX have an incubation period of 7 to 21 days before the onset of clinical manifestations [ 14 ], such as fever, headache, muscle aches, back pain, chills, rash, and lymphadenopathy [ 15 , 16 ]. Complications of MPX may include pneumonitis, encephalitis, visibly life-threatening keratitis, and secondary bacterial infections [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%